2000
DOI: 10.1007/bf03033799
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective strategies in parkinson’s disease: protection against progressive nigral damage induced by free radicals

Abstract: Brain undergoes neurodegeneration when excess free radicals overwhelm antioxidative defense systems during senescence, head trauma and/or neurotoxic insults. A site-specific accumulation of ferrous citrate-iron complexes in the substantia nigra dopaminergic neurons could lead to exaggerated dopamine turnover, dopamine auto-oxidation, free radical generation, and oxidant stress. Eventually, this iron-catalyzed dopamine auto-oxidation results in the accumulation of neuromelanin, a progressive loss of nigral neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 131 publications
(160 reference statements)
0
31
0
1
Order By: Relevance
“…Increased cytosolic DA is in turn easily oxidized and reactive oxygen species (ROS), including DA quinones, are produced (LaVoie and Hastings, 1999). Such increase in cytosolic DA will therefore result in decreased DA in the vesicles and ROS-mediated toxicity to DA neurons (Chiueh et al, 2000). Of the 3 metabolites examined, only DACT was found to be ineffective in alteriong synaptosomal or vesicular uptake of DA.…”
Section: Discussionmentioning
confidence: 99%
“…Increased cytosolic DA is in turn easily oxidized and reactive oxygen species (ROS), including DA quinones, are produced (LaVoie and Hastings, 1999). Such increase in cytosolic DA will therefore result in decreased DA in the vesicles and ROS-mediated toxicity to DA neurons (Chiueh et al, 2000). Of the 3 metabolites examined, only DACT was found to be ineffective in alteriong synaptosomal or vesicular uptake of DA.…”
Section: Discussionmentioning
confidence: 99%
“…In Parkinson's disease (PD) the role of neuromelanin as either an accelerant to neurotoxicity or as a neuroprotectant for pars compacta dopaminergic neurons is unresolved (Wilczok et al, 1999;Chiueh et al, 2000;Gerlach et al, 2000;Kostrzewa, 2000;Solano et al, 2000;Sulzer and Zecca, 2000;Double et al, 2003). Neuromelanin-containing neurons are apparently more susceptible to cell death (Marsden, 1983).…”
Section: Neuroprotection Neuromelanin and Neurodegenerationmentioning
confidence: 99%
“…Considerable insights into the pathogenesis of PD, indeed, have been achieved by use of the neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), which is commonly used to induce an experiment model of PD [105,107]. Excessive free radical formation or antioxidant deficiency and the resulting oxidative stress are all mechanisms involved in MPTP neurotoxicity [108]. Rajeswari [109] has shown that curcumin protects rat brain from MPTP-induced neurotoxicity by virtue of its scavenger activity.…”
Section: Curcumin and Neurodegenerative Disordersmentioning
confidence: 99%